2011
DOI: 10.3346/jkms.2011.26.12.1619
|View full text |Cite
|
Sign up to set email alerts
|

Korean-Specific Parameter Models for Calculating the Risk of Down Syndrome in the Second Trimester of Pregnancy

Abstract: The purpose of the current study was to propose a Korean-specific parameter set for calculating the risk of Down syndrome in the second trimester of pregnancy and to determine the screening performances of triple and quadruple tests in Korean women. Using the data on triple or quadruple screening from three hospitals in Korea during 7 yr, we re-converted the concentrations of four serum markers to multiple of median values according to gestational age and maternal weight. After re-calculating the risk of Down … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…The prevalence of DS in our study was considerably lower than in previous studies conducted in Korea. The prevalence of DS was 14 and 26.7 per 10,000 total births in Shin et al ( 18 ) and Jun et al ( 19 ), respectively. However, since two previous studies were limited to only a few institutions and not nationwide, it may not reflect the overall prevalence of DS in Korea.…”
Section: Discussionmentioning
confidence: 87%
“…The prevalence of DS in our study was considerably lower than in previous studies conducted in Korea. The prevalence of DS was 14 and 26.7 per 10,000 total births in Shin et al ( 18 ) and Jun et al ( 19 ), respectively. However, since two previous studies were limited to only a few institutions and not nationwide, it may not reflect the overall prevalence of DS in Korea.…”
Section: Discussionmentioning
confidence: 87%
“…Using these median analyte values, the grand median MoM for each of the three parameters (without regard for the gestational week) was always 1.00. Figure 1 compares Egyptian medians with those in Korea [15] and a number of Western areas compiled by Vranken et al [16] .…”
Section: Resultsmentioning
confidence: 99%
“…Weight distribution in our community is different from that in Western, black or Asian communities, and needs to be considered when adjustments to MoMs are to be made. Three formulas were derived and served to adjust measured MoMs to a population median maternal weight of 78.2 kg (compared to 60 kg in a Caucasian-based study [23] and 57.2 kg in a Korean study) [15] . A difference in median weight as small as 2.5 kg was recommended to warrant formula modification to minimize errors in risk calculation [24] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, only few studies have been reported regarding the reference values of these four second-trimester serum markers analyzed by an automated immunoassay among Asian population. 7,8 Moreover and importantly, no data derived from an automated immunoassay is available for Thai population. Accordingly, the aim of this study was to determine the median values of second trimester serum markers as a function of gestational age (GA) in Thai population using an automated immunoassay.…”
Section: Introductionmentioning
confidence: 99%